2018
DOI: 10.1016/j.jid.2017.12.010
|View full text |Cite
|
Sign up to set email alerts
|

LMO4 Is a Disease-Provocative Transcription Coregulator Activated by IL-23 in Psoriatic Keratinocytes

Abstract: Psoriasis is an autoimmune disease characterized by abnormal differentiation and hyperproliferation of epidermal keratinocytes. LIM-domain only protein 4 (LMO4) is a transcription factor coregulator that promotes the assembly of multiprotein complexes to regulate mammary epithelium and keratinocyte differentiation and proliferation during embryogenesis. In this study, LMO4 has been found to be abundantly expressed in psoriatic epidermis. LMO4 expression is increased in human keratinocytes induced to differenti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 55 publications
2
13
0
Order By: Relevance
“…Murine keratinocytes also produce biologically active IL-23 [130]. IL-23 can promote keratinocyte growth and histological acanthosis via the JAK2/AKT/STAT3/LMO4 signaling pathway [131]. LIM-domain only protein 4 (LMO4) is a LIM-domain protein that regulates keratinocyte proliferation and differentiation during embryogenesis [131].…”
Section: Il-17a and Psoriasismentioning
confidence: 99%
See 2 more Smart Citations
“…Murine keratinocytes also produce biologically active IL-23 [130]. IL-23 can promote keratinocyte growth and histological acanthosis via the JAK2/AKT/STAT3/LMO4 signaling pathway [131]. LIM-domain only protein 4 (LMO4) is a LIM-domain protein that regulates keratinocyte proliferation and differentiation during embryogenesis [131].…”
Section: Il-17a and Psoriasismentioning
confidence: 99%
“…IL-23 can promote keratinocyte growth and histological acanthosis via the JAK2/AKT/STAT3/LMO4 signaling pathway [131]. LIM-domain only protein 4 (LMO4) is a LIM-domain protein that regulates keratinocyte proliferation and differentiation during embryogenesis [131]. In addition, TNF-α is an active stimulator of IL-23 production from keratinocytes in mice and possibly in humans [131].…”
Section: Il-17a and Psoriasismentioning
confidence: 99%
See 1 more Smart Citation
“…Some reports suggest that the psoriatic epidermis shows an altered calcium metabolism, there exist specific defect of calcium influx and reduced [Ca 2+ ] i in psoriatic KCs, calcium can significantly inhibit the proliferation of KCs, and high calcium can result in a reduced proliferation of psoriatic KCs. [ 21 22 ] Our results indicated that STAT3 siRNA induced the elevation of [Ca 2+ ] i of psoriatic KCs significantly. The siRNA carried by Lipofectamine 3000 combined with ultrasonic irradiation and SonoVue microbubbles showed higher calcium fluorescence intensity mean which indicated [Ca 2+ ] i compared with that only carried by Lipofectamine 3000.…”
Section: Discussionmentioning
confidence: 71%
“…We projected the transcriptomic transition of individual T cell subsets approaching and leaving this branching onto a heatmap, which allowed us to discover signature gene features that make up this branching point ( Figure 4E ). A cluster of 13 genes were identified; 11 of 13 of these genes were signature genes identified in the T helper 17 cell (Th17) lineage, including the effector molecule Il17f and the master transcription factor Rorc ( Chang and Dong, 2009 ; Ciofani et al, 2012 ; Gobert et al, 2018 ; Hu et al, 2013 ; Kim and Lee, 2015 ; Li et al, 2009 ; Skepner et al, 2014 ; Su et al, 2016 ; Tu et al, 2018 ; Zhou et al, 2016 ). These Tc17-like cells may serve as intermediate progenitors to separate T RM s located in the tumor or distant mammary gland mucosa.…”
Section: Resultsmentioning
confidence: 99%